Application Of Project-Based Differentiation Learning for The Development of Short Story Writing Skills in Junior High School Class IX - Muhammad Esa Pratama; Irma Suryani; Maizar Karim (Universitas Islam Negeri Palopo, 2025)
This study aims to describe the application of project-based differentiation learning in the development of short story writing skills in Grade IX junior high school students. This study uses descriptive qualitative methods with data collection techniques in the form of observation, interview, and document analysis. The results showed that the application of project-based differentiation learning allows students to develop writing skills optimally according to their individual needs and potentials. This strategy is also effective in improving creativity, understanding the structure of short stories, and students' expression skills in writing. Thus, project-based differentiation learning can be an innovative alternative to writing learning at the junior high level.